Hollywood singing and dancing : [videorecording (DVD)] : a musical history - Jones, Shirley, 1934 March 31-; McLaughlin, Mark G.; Dye, Phillip; Hamilton, Denise; Lowe-Newsome, Tasha (Great Musical Treasure, 2008)
One of the most comprehensive films about the Hollywood musical ever produced. Screen and television icon Shirley Jones hosts this entertaining and historical document illustrated by extraordinary clips and fabulous interviews.